PERILAKU MASYARAKAT MISKIN DI KOTA BENGKULU DAN MODEL PENGENTASAN KEMISKINAN BERBASIS NILAI SOSIAL-BUDAYA - Hajar G. Pramudyasmono Paulus Suluk Kananlua Hasan Pribadi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
This article is written based on a research finding conducted in Bengkulu City. The goals of the research are to find out behavior of poor community contributed to persistant povery, and to formulate an alternative model for poverty alleviationsuitable to local social-cultural value. The respondents were selected using purposive sampling method, covering poor fishermen, vendors/small micro business, and blue colar labors/casual workers, in which each group consists of 20 people either the head of household or house-wife. The data were collected through observation and interviews. Qualitative approach was used to analyze the data. The finding shows that poor community in Bengkulu City tends to behave thrifly (consumptively), is used to owing to private money lender as well as neighbour's kiosk, and prefers to purchase goods in credit/instalment. Based on the data analysis, this research purposes three kinds of different poverty alleviation model forcommunity of fishermen, vendors, and casual workers.